Clinical features of neonatal hyperthyroidism: a retrospective analysis in southwestern China - Song, Yan; Wei, Hong; Cao, Luying; Deng, Pinglan; Du, Weixia; Liu, Shan; Zhang, Yu (Frontiers in Pediatrics, 2024)
Purpose This study aimed to explore the clinical characteristics and evaluate the different types of thyroid dysfunction in babies with neonatal hyperthyroidism. Methods The clinical data of 19 neonates with hyperthyroidism admitted to the Children's Hospital of Chongqing Medical University between January 2012 and April 2021 were retrospectively analyzed. Results Fifteen (78.9%) infants were born to mothers with Graves’ disease. Eleven (57.9%) infants were premature; two babies were born at small for gestational age. The age at diagnosis ranged from 3 to 34 days, with a mean of 18.53 ± 6.85 days. The majority of the babies presented with goiter (84.2%) and tachycardia (94.7%) after birth. Nine (47.4%) of them presented with abnormal weight gain, seven (36.8%) presented with stare or ocular protrusion, six (31.6%) presented with hyperexcitability, four (21.1%) presented with jaundice and liver dysfunction, two (10.5%) presented with sweating, one (5.3%) presented with fever, and one case presented without any symptoms. Transient hyperthyroidism was the main thyroid dysfunction in our study. Overt hyperthyroidism was diagnosed in 13 (68.4%) neonates. Another three babies (15.8%) presented with hyperthyroidism with slightly elevated free triiodothyronine levels, normal thyroxine (T4) levels, and low thyroid-stimulating hormone (TSH) levels. Normal thyroid hormone levels with low TSH levels were observed in three (15.8%) neonates. Ten children were treated with antithyroid drugs. Eighteen children recovered normal thyroid function at 1–3 months of age; one baby in the study group required further levothyroxine supplementation due to primary hypothyroidism (HT). One child was found to have developmental delay at 2 years of age during follow-up. Conclusions Our study highlights the need for prolonged monitoring of thyroid function in suspected patients. A single normal screening for hyperthyroidism or the absence of a maternal history of hyperthyroidism cannot exclude this disease.